Education human resources planning in developing excellent Madrasah in Madrasah Aliyah (MA) Darul Hikmah Tulungagung Indonesia - Hidayah, Ma'rifatul; Qomar, Mujamil; Sulistyorini, Sulistyorini; Sujianto, Agus Eko; Turmudzi, Imam (Technium Social Sciences Journal, 2021)
This research is motivated by quality human resource planning that can be created through Madrasah educational institutions as formal education providers. Madrasah gains the public's trust in preparing and delivering the nation's generation of children to be able to compete in global competitions whose impact is increasingly being felt in social life. Educational human resource planning is the most important element in every educational institution, the success of the institution in achieving its goals and various targets as well as its ability to face various challenges, both internal and external, is largely determined by the ability to manage human resources as precisely as possible. This proves that Madrasahs need human resource management in the field of education, with their managerial and operational functions, and supported by competent educators and education staff, so Madrasahh will have the power to grow, be productive, and competitive. The approach in this research is qualitative. Data collection techniques using in-depth interviews, participant observation, and documentation. Data analysis techniques using data condensation, data presentation, and drawing conclusions or verification. Checking the validity of the data by using triangulation methods, data sources, and theories. The findings of this study indicate that education human resource planning in developing superior Madrasah has carried out internal and external analysis with a needs analysis model, recruitment system, and selection system based on Khidmah.